Effect of Silica Addition on Mechanical Properties of Eggshell-Derived Hydroxyapatite - Fatma, Fatma; Desnelli, Desnelli; Riyanti, Fahma; Kamal, Mustafa; Mannan, Muhammad Ramdan Abdul; Hariani*, Poedji Loekitowati (Graduate School of Universitas Syiah Kuala, 2021)
Eggshell is a solid waste that is available in abundance but is being left unused. Eggshell containing calcium in a high amount. Calcium can be used as a precursor for hydroxyapatite (HAp). Modification of HAp with SiO2 is expected to improve its low mechanical properties for biomedical applications. In this study, HAp is synthesized from the eggshell. Then, it was modified by adding SiO2 utilizing the coprecipitation method with concentrations of 10%, 20%, 30%, and 40%, respectively. The HAp and HAp/SiO2 were characterized using; X-ray diffraction and Fourier transform infrared spectroscopy. The analysis HAp and HAp/SiO2 were density, compressive strength, and hardness. The best mechanical properties of HAp/SiO2 were characterized using SEM-EDS. The HAp were prepared successfully with a ratio of Ca/P was 1.673, close to the theoretical 1.67. The addition of SiO2 caused a decrease in crystallite size and density but increased compressive strength and hardness. The best mechanical properties of HAp/SiO2 were obtained with SiO2 of 30% and 40% with similar values.